1968
DOI: 10.1021/bi00847a029
|View full text |Cite
|
Sign up to set email alerts
|

Primary photochemistry and electron transport in Rhodospirillum rubrum

Abstract: Fl- .photoxidation, a quantum yield of 0.95 ± 0.05 was determined for production of the primary oxidized species called P 870 or P0.44. The extent of the cytochrome c photoxidation could be significantly increased by adding horse heart ferrocytochrome c and 1.5%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 32 publications
5
39
0
Order By: Relevance
“…13A~ In Chromatiwn a somewhat higher potential of 0.49 V for P870 has been reported by Cusanovich, BarL~ch and Kamen (1968). Loach and Sekura (1967) showed that the decay kinetics of the photoinduced absorption changes owing to P870 are identical to those of the EPR signal.. further kinetic and stoichiometric evidence supporting the identification of P870+ as oxidized BChl and responsible for the EPR signal was reported by Bolton, Clayton and Reed (1969) and by McElroy, Feher and ~huzerall (1969). Fig.…”
Section: 3 Trapping Times Deduced From Fluorescence Measurementssupporting
confidence: 55%
See 2 more Smart Citations
“…13A~ In Chromatiwn a somewhat higher potential of 0.49 V for P870 has been reported by Cusanovich, BarL~ch and Kamen (1968). Loach and Sekura (1967) showed that the decay kinetics of the photoinduced absorption changes owing to P870 are identical to those of the EPR signal.. further kinetic and stoichiometric evidence supporting the identification of P870+ as oxidized BChl and responsible for the EPR signal was reported by Bolton, Clayton and Reed (1969) and by McElroy, Feher and ~huzerall (1969). Fig.…”
Section: 3 Trapping Times Deduced From Fluorescence Measurementssupporting
confidence: 55%
“…At room temperature the quantum yields are close to unity for both the P870 change (Leach and Sekl1ra, 1968;Parson, I 1968;Beugl ing, 1968;Bolton et al, 1969;Clayton, Fleming and Szuts, 1972;Clayton, Szuts and Fleming, 1972;Slooten, 1972) and for the EPR I signal (Loach and Walsh, 1969;Weaver and Weaver, 1969;Loach and Hall, 1972) 'for chromatophores and reaction center preparations. 1he quantum yield of the P87p bleaching is changed hardly at all c..t l°K (Clayton, !…”
Section: 3 Trapping Times Deduced From Fluorescence Measurementsmentioning
confidence: 86%
See 1 more Smart Citation
“…The unpaired spin is delocalized over a special pair of bacteriochlorophyll molecules. That the signal is produced in the primary quantum conversion reaction in which the special pair functions as the primary donor is suggested by the measured quantum yield for the signal production (Loach and Walsh, 1969) and for the oxidation of P870 (Loach and Sekura 1968;Wraight and Clayton, 1973). The measured values are near unity.…”
Section: Primary Donormentioning
confidence: 96%
“…It is well established for most bacteria that a c-type cytochrome is the secondary component which donates electrons to the oxidized primary donor 617 I 1 1 1 1 1 1 (Duysens, 1954;Chance and Smith, 1955;Olson and Chance, 1960;Clayton, 1962;Morita et al, 1965;Loach and Sekura, 1968;Cusanovich r't al., 1968). In addition, it has been shown that h-type cytochromes (Nishimura and Chance, 1963;Ke and Ngo, 1967;Dutton and Jackson, 1972;Evans and Crofts, 1974;Knaff and Buchanan, 1975;Prince and Dutton, 1975), iron-sulfur proteins (Shanmugan and Arnon, 1972) and ubiquinone (Clayton, 1962a;Clayton and Straley, 1972;Slooten, 1972;Romijn and Amesz, 1975) are involved in bacterial electron transport reactions.…”
Section: Introductionmentioning
confidence: 99%